Blocking the cytohesin-2/ARF1 axis by SecinH3 ameliorates osteoclast-induced bone loss via attenuating JNK-mediated IRE1 endoribonuclease activity. (November 2022) - Dong, Yimin; Song, Kehan; Wang, Pengju; Guo, Jiachao; Kang, Honglei; Tan, Xi; Zhu, Binxiang; Peng, Renpeng; Zhu, Meipeng; Yu, Kaixu; Guo, Qian; Guan, Hanfeng; et al.
Abstract: cytohesin-2 is a guanine nucleotide exchange factor to activate ARF1 and ARF6, which are involved in various biological processes, including signal transduction, cell differentiation, cell structure organization, and survival. Nevertheless, there is a lack of evidence revealing the role of cytohesin-2 in osteoclast differentiation and in the development of osteoporosis. In this study, we find cytohesin-2 and ARF1 positively regulate osteoclast differentiation and function. Blocking the cytohesin-2 /ARF1 axis with SecinH3 or by genetic silencing of cytohesin-2 inhibits osteoclast formation and function in vitro. In vivo treatment with SecinH3 ameliorates ovariectomy-induced osteoporosis. Mechanistically, RNA-sequencing combined with molecular biological methodologies reveal that the regulatory function of cythohesin-2/ARF1 axis in osteoclast differentiation is mainly dependent on activating the JNK pathway. Further, in addition to the common viewpoint that JNK is activated by IRE1 via its kinase activity, we found that JNK can act upstream and regulate the endoribonuclease activity of IRE1 to promote XBP1 splicing. Both SecinH3 and silencing of cytohesin-2 inhibit JNK activation and IRE1 endoribonuclease activity, leading to the suppression of osteoclast differentiation. Taken together, our findings add new insights into the regulation between JNK and IRE1, and reveal that inhibiting the cytohesin-2/ARF1/JNK/IRE1 axis might represent a potential new strategy for the treatment of post-menopause osteoporosis. Graphical Abstract: ga1